A multi-technique surface study of the mercury(II) chalcogenide ion-selective electrode in saline media - De Marco, Roland; Pejcic, Bobby; Prince, K.; Van Riessen, Arie (The Royal Society of Chemistry, 2003)
X-ray photoelectron spectroscopy (XPS), secondary ion mass spectroscopy (SIMS), rotating disc electrode - electrochemical impedance spectroscopy (RDE-EIS) and synchrotron radiation - grazing incidence X-ray diffraction (SR-GIXRD) have been used to study the response mechanism of the mercury(II) chalcogenide ion-selective electrode (ISE) in saline media. XPS and SIMS have shown that the chalcogenide surface is poisoned by silver chloride, or a mixture of silver halides, on continuous exposure to synthetic and real seawater. Significantly, the in-situ SR-GIXRD study demonstrated that electrode fouling in synthetic seawater is linked to the formation of poorly crystalline or amorphous silver chloride, and that the low level of free mercury(II) in a calibration buffer (i.e., 10-14 M) is able to undergo metathesis with silver(I) sulfide in the membrane generating mercury(II) sulfide. Significantly, the results of this detailed surface study have shown that silver chloride fouling of the electrode is ameliorated in real seawater comprising natural organic ligands, and this has been attributed to the peptization of silver chloride by the surfactant-like nature of seawater ligands at pH 8. RDE-EIS aging studies have revealed that the chalcogenide membrane experiences a sluggish charge transfer reaction in seawater, and contrary to a previous report for a static electrode, the seawater matrix does not passivate the RDE. The results of this XPS, SIMS, RDE-EIS and SR-GIXRD study have elucidated the response mechanism of the mercury(II) ISE in saline media.